Peran Guru dalam Menerapkan Kurikulum Al-Islam Kemuhammadiyahan di Taman Kanak-Kanak Aisyiyah Bustanul Athfal Palopo - Duriani Duriani; Abdul Kadir (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The aim of this study is to understand the role of educators or teachers in implementing the curriculum of Al-Islam Kemuhammadiyahan in the Aisyiyah Children's Park Bustanul Athfal Palopo. Methods are used through qualitative research with a phenomenological approach. In this study, the head of the school and the teacher were six informants. Located at Aisyiyah Bustanul Athfal I, II, and II schools in Palopo Data collection methods involve observations and in-depth interviews, while data analysis is done by applying triangulation. The results of the research showed that (1) the learning planning on the curriculum of Aisyiyah Bustanul Athfal City Palopo School involves the semester activity plan, weekly activity plan, and time allocation. During two semesters of 34 weeks, the curriculum covers a wide range of themes, such as Me, My Family, Environment, Animals, Plants, Vehicles, the Universe, and My Country. These themes are scattered into diverse sub-themes, tailored to a variety of children's developmental environments. (2) Implementation of learning on the curriculum of Bustanul Athfal Palopo is carried out through several learning methods, including methods of giving examples, the method of listing, the method of advice, prohibitions, and orders, as well as methods of experiencing physically and internally, applied by the teacher based on the plan of implementation of daily learning.